Cerebral Edema in a Child after Preemptive Kidney Transplantation - Kakajiwala, Aadil; Weiss, Scott; Lopez, Sonya; Palmer, Joann; Baluarte, Hobart Jorge (Journal of Pediatric Intensive Care, 2017)
Dialysis disequilibrium syndrome (DDS) is characterized by acute neurological manifestations in patients undergoing first dialysis treatment. The mechanisms for the development of DDS include the reverse urea effect, transient intracranial acidosis, and idiogenic osmoles which can increase intracellular osmolality and promote water movement into the brain. We present a case of a 4-year-old child with chronic kidney disease who underwent a preemptive living unrelated donor kidney transplant. He had a 24 mEq/L drop in his sodium concentration, 92% reduction in blood urea nitrogen (BUN) concentration, and a 67 mOsm/kg drop in serum osmolality within 18 hours after transplant, with concurrent development of symptomatic and radiologic cerebral edema, similar to that described in DDS. Mental status rapidly returned to baseline after administration of 3% hypertonic saline. This case highlights the risk of cerebral edema in patients who have a high pretransplant BUN. It emphasizes the need for close monitoring of vital signs, mental status, and electrolytes in children undergoing renal transplant. Hypertonic solutions can be used to prevent or manage cerebral edema in these patients when serum osmolality decreases rapidly. Pretransplant dialysis is another consideration to proactively reduce serum hyperosmolality.
Keywords: renal transplant; fluid management; hyponatremia; osmolality; dialysis disequilibrium syndrome